Lipidomic Insight of Anticandidal Perillyl Alcohol and Sesamol Induced Candida Membrane Disruption: Implications of Lipid Alteration, Impaired Fluidity and Flippase Activity - Fatima, Zeeshan; Hameed, Saif (Infectious Disorders - Drug Targets, 2020)
Background: Considering the emergence of multidrug resistance (MDR) in prevalent human fungal pathogen, Candida albicans, there is parallel spurt in the development of novel strategies aimed to disrupt MDR. The cell envelope of C. albicans comprises a wealth of lipid moieties contributing towards long-term survival of pathogen that could be exploited as efficient antifungal target owing to the advancements made in mass spectrometry based lipidomics technology. Objective: This study aimed to utilize the lipidomics approach to unveil several lipid-associated changes in response to two natural anticandidal compounds perillyl alcohol (PA) and sesamol (Ses). Methods: Lipidomics is performed through ESI-MS, flippase activity by FACS, fluorescence spectrometric analysis is used to assess membrane fluidity. Results: Lipidomic analyses revealed that phosphatidylcholine (PtdCho) were decreased in the presence of Ses with considerable differences at specie level. Concurrently, we explored increased inward translocation (flip) of fluorophore labelled PtdCho across the plasma membrane attributed to enhanced PtdCho specific flippase activity. A considerable decrement in phosphatidylethanolamine (PtdEtn) leading to altered membrane fluidity was observed in response to PA and Ses. Additionally, we could detect alteration in the levels of phohatidylserine (PtdSer) and phosphatidylglycerol (PtdGro) along with decreased triacylglycerides (TAG). The differential expressions of various lipid biosynthetic pathway genes by RT-PCR corroborated with the lipidomics data. Furthermore, PA and Ses leads to potentiation of membrane targeting drugs (azole and polyene) and displayed additive effect. Conclusion: Our work offers the basis of further understanding the regulation of lipid homeostasis in C. abicans so that better therapeutic targets could be identified to combat MDR.
Keywords: Candida